Ideas, Truth And Importance Of Mahatma Gandhi’s Philosophy Towards Concept Of Non-Violence (Journal of Namibian Studies : History Politics Culture, 2023)
Mahatma Gandhi's philosophy of nonviolence, or ahimsa, was fundamental to his methodology of conflict resolution. He perceived nonviolence as a harmonious approach to thinking, feeling, and behaving that repudiates exploitation and violence. His notion of satyagraha, or steadfast adherence to truth, encompassed peaceful resistance to injustice via strategies including non-cooperation and civil disobedience. Nonviolence is a philosophy, a theoretical framework, a practice, a lifestyle, and a method of social, political, and economic struggle that has existed throughout history. Mahatma Gandhi highlighted the nonviolence of the powerful as opposed to that of the weak while elucidating its significance and consequences. Although nonviolence acknowledges the capacity to use physical force for the defense of one's rights, practitioners opt to harness their spiritual might against their aggressors. Throughout history, individuals have rejected violence as a method for settling conflicts. Gandhi claimed that reason and conscience may influence adversaries to alter their positions, rendering violence superfluous. Nonetheless, some contend that Gandhi's nonviolence had boundaries; he permitted violence in some instances and acknowledged that reason alone was inadequate for social transformation. Although Gandhi's nonviolence significantly influenced society, a close examination uncovers contradictions and ambiguities within his worldview.In this article ideas, truth and importance of Mahatma Gandhi’s philosophy towards concept of non-violence has been discussed.